BREASTFEEDING, SKIN‐TO‐SKIN CONTACT, AND MOTHER–INFANT INTERACTIONS OVER INFANTS' FIRST THREE MONTHS. Issue 1 (4th November 2013) - Bigelow, Ann E.; Power, Michelle; Gillis, Doris E.; Maclellan‐Peters, Janis; Alex, Marion; McDonald, Claudette
ABSTRACT The effects of skin‐to‐skin contact (SSC) on the maintenance of mothers' decision to breastfeed, the effects of breastfeeding and SSC on mother–infant interactions, and whether maternal depressive symptoms mediate these effects were investigated over infants' first 3 months. When infants were 1 week, 1 month, 2 months, and 3 months of age, mothers in the SSC and control groups reported the type of infant feeding provided and completed the Edinburgh Postnatal Depression Scale (EPDS; J.L. Cox, J.M. Holden, & R. Sagovsky, 1987); mother–infant interactions were coded on the Nursing Child Assessment Feeding Scale (NCAFS; G. Summer & A. Spietz, 1994). Percentage of breastfeeding dyads in the SSC group was stable over the 3 months; yet, fewer dyads in the control group were breastfeeding at the 2‐ and 3‐month visits than at the 1‐week visit. Breastfeeding dyads had higher NCAFS Caregiver subscale scores, indicating more positive maternal interactions, at 1 week, 2 months, and 3 months. NCAFS scores did not differ for the SSC and control groups. EPDS scores did not mediate the effect of SSC on breastfeeding or breastfeeding on NCAFS Caregiver subscale scores.